The effect of distraction by bubble-making on the procedural anxiety of injection in Thalassemic school- age children in Kerman Thalasemia center - Bagherian, Samaneh; Borhani, Fariba; Abbas Zadeh, Abbas; Ranjbar, Hadi; Solaimani, Farzaneh (Advances in Nursing & Midwifery, 2012)
Background and aim: Medical procedures, particularly injection, cause anxiety in children. Coping with invasive medical treatment is an important issue for all children, particularly chronically ill children such as thalassemic children who may have to endure many treatment procedures. This study examined the effect of breathing exersice on the anxiety resulted from the injection procedure in thalassemic school-age children in Kerman thalassemia center Materials and Methods: In this clinical trial, 40 thalassemia children with 6-12 years old, in Kerman thalasemia center were selected through convenience sampling method. Then subjects were randomly allocated in two groups (experimental group and control group). In experimental group, bubble making was used. Data collection tools were: Demographic Information Questionnaire, and the Scale of facial self reported anxiety. The analysis of the data was carried out through SPSS 16. Findings: Average score of anxiety in bubble making group was 2.9+1.5 before and 1.0+1.1 after injection. The average score in control group was 3.1+2.2 before and 2.4 + 2.1after injection. There was no significant difference between two groups of study regarding the average scores of anxiety before the injection (p>0.05) but there was a significant difference between two groups regarding the average scores of anxiety after the injection (p>0.05). Conclusion: The results of this study showed that bubble making is an effective method to decrease anxiety resulted from the injection procedures. Key words: Anxiety, Bubble making, School-age Children, Distraction, Thalassemia